Beyond "to Share or Not to Share": The Impartiality Account of Fairness. (October 2013) - Shaw, Alex
Fairness concerns often prompt people to share equally, but the function of such equal sharing is somewhat unclear. Some researchers have proposed that fairness functions to promote generosity and reciprocity. I will review some recent data that contradict this view: Fairness can cause people to waste resources rather than be generous and can interfere with reciprocity. On the basis of these findings, I suggest an alternative view: Fairness functions to signal the fair individual's impartiality to others. I discuss the predictions of this account and how these predictions might be tested in future research.